(untitled) (Research, Society and Development, 2022)
The objective of the present work was to evaluate the effect of different levels of organic fertilization on the emergence and growth of yellow passion fruit seedlings under semi-arid conditions. The experiment was carried out using a completely randomized block design, in a 3:5 factorial arrangement consisting of three organic compounds [humus (HU), goat manure (EC) and sugarcane filter cake (TCA)] and five levels of fertilization (T1 = 100% of soil; T2 = 20% of compost + 80% of soil; T3 = 40% of compost + 60% of soil; T4 = 60% of compost + 40% of soil; and T5 = 80 % of compost + 20% of soil), arranged in 3 blocks with 30 repetitions per plot. Parameters referring to emergence and initial growth of passion fruit plants were evaluated. The evaluation of the data of each treatment showed that the use of 56% of humus, 48% of TCA and 41% of goat manure promoted the best results of emergence and growth of seedlings and gas exchange. However, the comparison of the three organic compounds indicated that the treatment with 56% of humus promoted better performance of the parameters growth and of fresh and dry mass, showing to be a good option for the production of seedlings with organic fertilization.